2019
DOI: 10.1088/1361-6471/ab1a56
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of proton radioactivity based on Gamow-like model with a screened electrostatic barrier

Abstract: In the present work we systematically study the half-lives of proton radioactivity for 51 ≤ Z ≤ 83 nuclei based on the Gamow-like model with a screened electrostatic barrier. In this model there are two parameters while considering the screened electrostatic effect of Coulomb potential with the Hulthen potential i.e. the effective nuclear radius parameter r 0 and the screening parameter a. The calculated results can well reproduce the experimental data. In addition, we extend this model to predict the proton r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…In the Fig. 5, the calculated half-lives are evaluated by the present method, UDLP [41] and Gamow-like model [13] without Fig. 5 Decimal logarithm deviations between the experimental data of proton radioactivity half-lives and calculations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Fig. 5, the calculated half-lives are evaluated by the present method, UDLP [41] and Gamow-like model [13] without Fig. 5 Decimal logarithm deviations between the experimental data of proton radioactivity half-lives and calculations.…”
Section: Resultsmentioning
confidence: 99%
“…Klepper et al [4] a e-mail: lixiaohuaphysics@126.com (corresponding author) b e-mail: wuxijun1980@yahoo.cn c e-mail: kyois@126.com and Faestermann et al [5] observed proton emission from the ground state of 147 Tm and 109 I, 113 Cs in 1982 and 1984, respectively. With the development of advanced experimental facilities and radioactive beams, an increasing number of proton emissions from the ground state or low isomeric states have been discovered in the proton regions Z = 50 − 82 [6][7][8][9][10][11][12][13]. As an important decay mode of unstable nuclei, proton radioactivity is an useful tool to obtain spectroscopic information because the decaying proton is the unpaired proton not filling its orbit, and extract information on nuclear structure and the internuclear potential [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] observed proton emission from the ground state of 147 Tm and 109 I, 113 Cs in 1982 and 1984, respectively. With the development of advanced experimental facilities and radioactive beams, an increasing number of proton emissions from the ground state or low isomeric states have been discovered in the proton regions Z = 50 − 82 [6][7][8][9][10][11][12][13]. As an important decay mode of unstable nuclei, proton radioactivity is an useful tool to obtain spectroscopic information because the decaying proton is the unpaired proton not filling its orbit, and extract information on nuclear structure and the internuclear potential [14].…”
Section: Introductionmentioning
confidence: 99%
“…The proton radioactivity has the lowest Coulomb potential among all charged particles and mass being smallest it suffers the highest centrifugal barrier, enabling this process suitable to be dealt within WKB barrier penetration model [15]. Up to now, there are a lot of models having been put forward to deal with the proton radioactivity such as the effective interactions of density-dependent M3Y (DDM3Y) [16,17], the singlefolding model (SFM) [15,18], the generalized liquiddrop model (GLDM) [9,19,20], the phenomenological unified fission model (UFM) [21,22], the Coulomb and proximity potential model (CPPM) [10,23,24], the Gamow-like model (GLM) [13,25], the two-potential approach with Skyrme-Hartree-Fock (TPA-SHF) [26] and so on. As we all known, in the process of studying the charged particles radioactivity, selection of the emitted particle-nucleus interaction potential is key to improve the accuracy of half-life.…”
Section: Introductionmentioning
confidence: 99%